1994
DOI: 10.1002/edp.2430030106
|View full text |Cite
|
Sign up to set email alerts
|

Communication in preterm infants: Why is it different?

Abstract: The present paper selectively reviews the literature which compares full-term and pnkrm infants' communication with their mothers in the first year of life. The review is focused not only on what differences are found between full-term and preterm infants, but also why such differences exist. Particular emphasis is placed on the importance of inbrprethg the findings in the light of the developmental phase of the infants, the heterogeneity of the pmtum population and the situation in which communication is stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…This finding is in agreement with the observation of van Beek [16], who called this phenomenon ‘infant dominance’. However, occasionally infants followed mothers.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is in agreement with the observation of van Beek [16], who called this phenomenon ‘infant dominance’. However, occasionally infants followed mothers.…”
Section: Discussionsupporting
confidence: 93%
“…However, the reported data on the characteristics of the preterm mothers’ behaviors are inconsistent. In some studies the mothers of preterm infants were more active and responsive than mothers of full-term infants [14], [15], whereas other authors found the opposite: the preterm mothers were less active, less sensitive and responsive, and expressed fewer emotions [10], [13], [16].…”
Section: Introductionmentioning
confidence: 99%
“…Early social interaction between preterm infants and their parents depends on the characteristics and behavior of both infants and caregivers, and differs from that of full-term infants in different ways (4). Social interaction starts at an earlier age in their development when the infants are generally more immature and vulnerable and the medical conditions are different (60). The interaction takes place under the physical constraints of the NICU environment, often in the context of parental affects with shock, stress, grief and depression combined with guilt for the preterm birth and anxiety about infant's survival (55), and the ͳͺ parents have to relate to many health care providers of different professional background.…”
Section: 2 Social Interaction With Preterm Infantsmentioning
confidence: 99%
“…Very low birth weight is a risk factor for developmental delay, brain damage, epilepsy, mental retardation, motor and sensory deficits, poor academic performance, and delayed language development. [2][3][4][5] Gestational age, birth weight, and clinical complications are often associated. The shorter the duration of pregnancy and the lower the birth weight, the higher the likelihood of complications in the neonatal period.…”
mentioning
confidence: 99%